HAKIKAT MANUSIA MENURUT ISLAM - Isop Syafei (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2013)
According psychology-philosophy perspective, various pattern in education caused by different view about human being.. Abdurrahman an-Nahlawi stated that how human view about themselves will give strong effect toward education system.[1]. If human is viewed as creature with an evil talent, then education means as an effort to supress those evil factors.[1] On the other hands, if human is viewed as an active creature with potential, interest, and good basic competency, education means drawing out process in which taken out everything the children have not pouring in like water jar.